Flap Advancement Technique for Scalp Hair Preservation in Massive Cutis Verticis Gyrata - Javed, Bilal; Rao, Amina; Abdullah, Waleed; Amber, Akasha; Amin, Mughese (Indian Journal of Plastic Surgery, 2024)
Cutis verticis gyrata (CVG) is a rare skin condition characterized by ridges and furrows resembling the brain. CVG falls under three categories: primary essential, primary nonessential, and secondary. This case report focuses on primary essential CVG, where approximately a fourth of the scalp and a significant portion of the forehead and eyelid were involved.Flap advancement after skin expansion was performed to rectify the disorder. This technique adequately covers the residual defect postexcision and preserves hair growth in affected regions. It is a successful skin expansion technique to cover the exposed scalp, preserve hair growth, and achieve excellent cosmetic results. Our approach demonstrates a promising solution for severe cosmetic disfigurement in primary essential CVG, positively impacting both the physical appearance and psychosocial well-being of the patient.
Keywords: cutis verticis gyrata; tissue expansion; hair transplant